Periodic inhalation of carbon monoxide prior to repeated sprint training - a nuanced way for improving repeated sprint ability - Sundqvist, C. (The Ohio State University, 2022)
Background: Repeated sprint training in hypoxia has shown to be superior to training in normoxia. However, both natural and simulated altitude training are strategies that are not always accessible and expensive due to traveling or the need for advanced equipment. A possible way of simulating hypoxic conditions is to administer carbon monoxide (CO) prior to training as it has been shown to reduce the oxygen transport and delivery to the muscle similar to systemic hypoxia. It is therefore hypothesized that inhaling a small bolus of CO prior to repeated-sprint exercise will potentiate the acute physiological responses during the training, thus induce performance improvements associated with repeated sprint ability compared to placebo control.